Using Hermetia illucens larvae to process biowaste from aquaculture production - Lopes, Ivã Guidini [UNESP] (2020)
Aquaculture is a fast-growing activity that is generating increasing volumes of organic waste such as fish carcasses, which must be managed. In a study evaluating black soldier fly (BSF) larvae composting of this waste stream, we tested 21 combinations of reclaimed bread waste and aquaculture waste (with replacement increments of 5%). The best treatments were validated in a second experiment. Within 11–12 days of treatment, inclusion of 15% aquaculture waste increased larvae size by 35% and body protein content by 60% (45%DM) compared with larvae fed only bread waste. Bioconversion of materials was favored by the addition of aquaculture waste, reaching 18%DM. However, as revealed by a principal component analysis, 50.5% of the data variance was weighted by the addition of aquaculture waste in the treatments, negatively correlating to larvae survival, which declined as more of this waste stream was added. Nevertheless, the nitrogen content of the final compost increased as more aquaculture waste was added, while nitrogen volatilization varied slightly (max. 33% of total nitrogen). Overall, addition of small amounts (<15%) of aquaculture waste was demonstrated to be very beneficial for process performance in BSF larvae composting and for larval quality.